The new politics of home housing, gender and care in times of crisis - Jupp, Eleanor ca. 20./21. Jh; Bowlby, Sophie 1944-; Franklin, Janet 1959-; Hall, Sarah Marie ca. 20./21. Jh (Policy Press shorts, 2019)
Setting out both new empirical material and new conceptual terrain, this book draws on approaches from human geography, social policy, and feminist and political theory to explore issues of home and care in times of crisis